2012
DOI: 10.19173/irrodl.v13i1.968
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of virtual and open distance science teacher education in Zimbabwe

Abstract: This paper reports on a study of the implementation of science teacher education through virtual and open distance learning in the Mashonaland Central Province, Zimbabwe. The study provides insight into challenges faced by students and lecturers on inception of the program at four centres. Data was collected from completed evaluation survey forms of forty-two lecturers who were directly involved at the launch of the program and in-depth interviews. Qualitative data analysis revealed that the programme faces po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…Hollow and ICWE (2009) and Walimbwa (2008) identified lack of human capacity as one of the most notorious challenges impeding the adoption of e learning. Mpofu et al (2012) observed that the majority of the lecturers facilitating open, distance, and e-learning in Zimbabwe were not properly trained on open and distance learning as a mode of delivery and were not familiar with teaching in an online environment. Walimbwa (2008) observed that insufficient resources and an indifferent attitude, in particular, from the teaching fraternity were major hindrances in the adoption of e-learning in East African Universities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hollow and ICWE (2009) and Walimbwa (2008) identified lack of human capacity as one of the most notorious challenges impeding the adoption of e learning. Mpofu et al (2012) observed that the majority of the lecturers facilitating open, distance, and e-learning in Zimbabwe were not properly trained on open and distance learning as a mode of delivery and were not familiar with teaching in an online environment. Walimbwa (2008) observed that insufficient resources and an indifferent attitude, in particular, from the teaching fraternity were major hindrances in the adoption of e-learning in East African Universities.…”
Section: Discussionmentioning
confidence: 99%
“…While the developed world is increasingly embracing e-learning, the same is not true of Africa. According to Mpofu et al (2012), the adoption of e-learning in Africa is slow, as evidenced by the low number of African scholars who are familiar with teaching in an online environment. Hollow and ICWE (2009), reporting on a survey of 147 e-learning practitioners from 34 countries in Africa, observed that e-learning was developing at a slow pace due to many challenges that impede its adoption and utilization in the universities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A study held in Kenya by Nyerere et al (2012) revealed that the delivery of online learning faces infrastructural issues as one of the main handicaps, with students reporting low levels of satisfaction with the resource centres, programme organization and delivery. Likewise, in Zimbabwe, Mpofu et al (2012) found that distance learning was threatened by a lack of properly trained teaching staff. These scenarios still prevail in many other African countries, where the level of digital literacy or preparedness to use electronic devices and the internet coverage and access are yet to improve (Krönke, 2020;Nyerere, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this study uses the term ‘online learning’ in reference to e-learning. While online learning has been used in distance education at the University of Namibia (Mpofu et al 2012 ), COVID-19 provided the impetus for the University of Namibia to introduce online learning and teaching for contact programmes also. This drastic move was accompanied by the demand for enhanced online skills on the part of nurse educators.…”
Section: Introductionmentioning
confidence: 99%